Design and Development of Spring Stiffness Measuring Instrument - Patil, Sujit S.; Patil, Shubham; Lamb, Rohan; Redekar, Bhushan; Kavathankar, Achyut; Mane, Jotiram (Asian Review of Mechanical Engineering, 2018)
Springs are inevitable part in many mechanical systems. Currently spring stiffness measurement is carried out mostly using some mechanical devices with hydraulic systems and analog measuring instruments. But these systems are much more costly for smaller industries. This paper presents a work of designing and fabrication of a small scale spring stiffness measuring machine. Here load application is done by conventional method, i.e. using hydraulic system. Use of sound sensors instead of scales and gauges makes it more compact and less expensive than any other apparatus. Additionally, using electronic components make this system flexible for more add-ons and gives better user interface. All the components used for this system are available in low cost. At the end, the results of measurement of stiffness by using machine and by theoretical method are compared.